Sayyid Mawdudi’s approach to biblical reports: an analysis - Osmani, Noor Mohammad; Rahman, Muhammad Habibur (Hamdard Foundation, 2023)
Isra’iliyyat, or biblical reports undoubtedly play a key role in the interpretations of the Holy Qur’an. That is because Isra’iliyyat provide detailed information about the past Prophets (‘Alaihim As-Salam) in the Holy Qur’an. Since biblical reports can range from sound to weak and even baseless in strengths, the Quranic interpreters have diverse stances regarding their acceptance. The prime purpose of this study is to explore the stance of Sayyid Mawdudi towards biblical reports. Sayyid Mawdudi had a balanced approach to it. He did not reject it outright; nor did he accept it totally without examination. He remained extremely cautious in dealing with it. He clearly identifies the similarities and differences between the Holy Qur’an and the biblical reports; and in case of differences existing, decides on reports to be accepted. The study followed a textual analytical method to deal with the biblical reports quoted by Sayyid Mawdudi in his Tafsir. It also used the original biblical reports from the Bible’s New International Version, ‘Al-Kitab al-Muqaddas’ in Arabic, the Talmud, and the Jewish Encyclopaedia to refer to the original sources of biblical reports and their own explanation of it. The study concluded that biblical reports are indispensable parts of the interpretation of the Holy Qur’an. They should not be rejected outright, nor should they be accepted without 50 Sayyid Mawdudi’s Approach thorough investigation. When compared to all contemporary and traditional scholars, it is found that Sayyid Mawdudi had an ideal stance toward biblical reports.